Exploring the resistance mechanism of imipenem in carbapenem hydrolysing class D beta-lactamases OXA-143 and its variant OXA-231 (D224A) expressing Acinetobacter baumannii: An in-silico approach. (April 2017) - Malathi, Kullappan; Anbarasu, Anand; Ramaiah, Sudha
Graphical abstract: Molecular docking of imipenem with OXA-143 CHDL of Acinetobacter baumannii. OXA-143 CHDL - imipenem complex has higher binding interaction than OXA-231 CHDL - imipenem complex. The increased binding affinity of the imipenem against OXA-143 CHDL will increase the rate of hydrolysis and leads to the resistance. Highlights: Molecular docking and simulations are done for OXA-143 and OXA-231 CHDLs with imipenem. Imipenem has increased binding affinity with OXA-143 CHDL than OXA-231 CHDL. Molecular dynamics study reveals high stability of OXA-143 CHDL- imipenem complex. Lesser stability indicates the effectiveness of imipenem against OXA-231 CHDL. Abstract: Acinetobacter baumannii ( A. baumannii), is a Gram negative, coccobacilli and is associated with nosocomial infections. The bacterium has developed resistance to all known classes of antibiotics. Multi-drug resistant A. baumannii infections have been treated with the carbapenem group of antibiotics like imipenem and meropenem. Recent reports indicate that A. baumannii has acquired resistance to imipenem due to the secretion of carbapenem hydrolysing class D beta-lactamases (CHDLs). Such CHDLs found in carbapenem resistant A. baumannii belongs to OXA-143 and its variant OXA-231, which has Alanine (A) in place of Aspartic acid (D) at sequence position 224. The mutation of the OXA-231 CHDL alters the catalytic activity of the enzyme. Hence, the present study was carried out to find the probable mechanism of imipenem resistance in OXA-143 and OXA-231 (D224A) CHDLs expressing A. baumannii by employing molecular docking and dynamics. Methods Our study reveals that OXA-143 CHDL-imipenem complex has more binding affinity than OXA-231 (D224A) CHDL-imipenem complex. Our results indicate that there is a strong binding affinity of OXA-143 with imipenem when compared with OXA-243 and this mechanism might be the probable reason for imipenem resistance in OXA-143 expressing A. baumannii strains.